Proposed Marketing Strategy of PT. Pelabuhan Indonesia III (Persero) Property the Case of Tegal Port - Art’sera Esti Widiyastuti; Atik Aprianingsih (Journal of International Conference Proceedings (JICP), 2019)
The land is one of the principal capitals for the company to develop its business, plays a role in the manufacturing industries and industries that require land/ factory/ warehouse/ field support. However, it often happens and hinders the company's process; for example, there are land disputes by other parties. PT Pelindo III which is engaged in port services. The company has 43 ports spread across seven provinces, with total fixed assets of land around 2,439 Ha. Of the entire area remaining 23.16% or about 564 Ha which has not been used/ unemployed. The existence of vacant land can have an impact on the land is used by other parties and it will cause high costs, so the right marketing strategies are needed to be able to optimize the land. This research is conducted to understand the business environment of port’s property and to develop it’s marketing strategy. This research use data which taken from published reports, journals and other articles regarding to property, this research also using interview methods to the customer to finda out the marketing behavior. The result of this research is proposed marketing strategy to optimize land-use to be implemented by the company.